Boro na produtividade, estado nutricional e qualidade de frutos de tangerineira “Ponkan” - Loosli, Felipe Silva (2018)
In order to obtain adequate levels of productivity and quality in citrus, a balanced mineral nutrition is essential. The deficiency or the excess of some nutrient causes quantitative and qualitative losses in the production not only of citrus, but of any economic culture. Boron is a micronutrient closely linked to some functions of the plant, from the formation of a cell wall to the construction of reproductive organs, and the imbalance of this element mainly in flowering will lead to direct loss in fruit production. The objective of this work was to evaluate the influence of different doses of Boron on macro and micronutrient contents in leaves and fruits, as well as quality indexes and productivity of Ponkan tangerine. The present work was developed in the years 2016 and 2017, in a 12-year-old Citrumelo Swingle grafted orchard located in Campus II of Universidade do Oeste Paulista in the municipality of Presidente Prudente (SP). The following dosages were evaluated: 0, 1, 2, 3, 4, 5 kg ha-1 of boric acid. The experimental design was a randomized complete block design, containing 6 treatments with 5 replicates and 1 plant per plot. The parameters evaluated were the physical attributes, number of fruits, fruit size, average fruit mass and productivity (t ha-1) and chemical parameters Soluble solids, titratable acidity, and the 'ratio'. The results were submitted to analysis of variance to the Tukey test (p ≤ 0.05) by the SISVAR program. The results showed significant effects on fruit mass, soluble solids, fruit size and number of fruits per plant. The most efficient doses were 3, 4 kg ha -1 in the first year and 4.0 kg ha -1 in the second year.